Discussion on the ideas of the Two Gods by Paulos Huang, Guanghu He and Peng Yang - Huang, Paulos; He, Guanghu; Yang, Peng (International Journal of Sino-Western Studies, 2022)
I think Mr. Yang Peng’s lecture has made a great contribution to our understanding of the similarities and differences between the God in ancient Chinese books and the God in the Bible. It is very specific and real. The "seven characteristics" he summarized, summed up the attributes of God in the Bible or Christianity into seven characteristics, which I think is quite accurate: an adjective in front, a noun in the back, and adjectives are indispensable (if I have time later, I will explain it ), and the nouns are also very accurate (if I have time, I will also say my improvement opinions on his summary, which is more important in my opinion). He has done in-depth research on ancient Chinese books, such as paying attention to how many times "God" and "Heaven" appear in oracle bone inscriptions. This is a very real academic work, which I admire very much.